Kemampuan Trichoderma viride Isolat PP2 dalam Mengendalikan Colletotrichum gloeosporioides pada Tanaman Cabai (Capsicum annuum Linnaeus) secara In-Planta - Gefi Zulmiati Lannur; Yenni Liswarni; Martinius Martinius (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2021)
The culture filtrate is a secondary metabolite produced from the multiplication of fungi in a liquid medium during the incubation period, separated between the fungal cell and their supernatants. Trichoderma viride culture filtrate testing has been widely carried out and used as a biocontrol agent. This study aimed to determine the ability of Trichoderma viride PP2 culture filtrate concentration in suppressing anthracnose disease caused by C. gloeosporioides on the red chili pepper. The study was conducted with a randomized block design (RBD) consisting of 5 treatments and five replications. The treatments were the concentration of T. viride PP2 culture filtrate, i.e., 0% (control), 25%, 50%, 75% and 100%. Parameters observed were incubation period, percentage of infected, and infected intensity. The results showed that the application of filtrate of T. viride isolate PP2 with different concentrations has not been able to suppress the development of anthracnose disease caused by C. gloeosporioides in-planta. It is necessary to conduct further research on the effect of temperature and time application on suppressing the filtrate of T. viride isolate PP2.